FEATURES OF FORMING THE PSYCHOLOGICAL SAFETY OF THE EDUCATIONAL ENVIRONMENT OF AN EDUCATIONAL INSTITUTE - Dina H. Gurieva; Elena N. Rudneva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is devoted to the issue of finding out the factors of the psychological safety of the educational environment of an educational institute and the subjects of the education process. The relevance of the topic is shown from the point of view of the ongoing reforms and the modernization of all the levels of education. In the article, an analysis of research literature is given which allowed to single out the main approaches to the definition of the term “psychological safety of the educational environment”. The definitions of the terms “personal safety”, “factors of personal safety” were given. Two approaches were presented: the environmental and the personal approach which form the psychological safety of the education environment of an educational institute. The purpose of the research was to find out the possible factors of the psychological safety of the educational environment of an educational institute. 180 people took part in the research, among them the students and the teachers of Moscow medical college. In the research, the methods of “Psychological diagnostics of educational environment safety” (I.A.Bayeva) and “Diagnostics of educational environment psychological safety” (V.V.Kovrov, G.S.Kozhukhar) were used which allowed to define the relation of the respondents to the education environment of the institution, to evaluate the importance of the features of the education environment and how they satisfy the needs of the respondents, and to define the level of imuunity to the psychological violence during interaction. The results of the research allow to state the importance of the factors of the psychological safety of the education environment and their positive effect on all the participants of the education process of the education institute.